Legal Protection For Victims Of Trafficking In Persons From The Perspective Of National And International Law - Citra Sonia (JURIDISCH DENKEN, 2025)
Trafficking in persons (TPPO) is a serious issue that violates human rights, especially those affecting women and children. This research aims to analyze legal protection for victims and sanctions against perpetrators based on Law No. 21/2007 and international law such as the Palermo Protocol. Legal protection includes rehabilitation, compensation, repatriation of victims, and confidentiality of identity, as regulated in national and international law. The method used is normative with analysis of literature and legislation. The results show that protection for victims includes physical, psychological, social rehabilitation, compensation, and security, while sanctions against perpetrators include imprisonment, fines, and aggravation for certain cases. Effective sanctions and comprehensive protection are needed to prevent and handle TPPO in Indonesia. Protection of victims' rights needs to be optimized so that they get proper restitution and rehabilitation. Keywords: Human Trafficking Crime, Legal Protection, Legal Sanctions.